Carpal Tunnel Syndrome in Patients with Psoriatic Arthritis; Superb Microvascular Imaging Findings - Akyildiz Tezcan, Ezgi; Levendoglu, Funda; Durmaz, Mehmet Sedat; Balevi Batur, Elif; Albayrak Gezer, Ilknur (Aktuelle Rheumatologie, 2023)
Background It is well known that the carpal tunnel syndrome (CTS) is the most widespread peripheral nerve entrapment syndrome throughout the world. CTS can also be seen more often in rheumatic disease, especially in psoriatic arthritis (PsA). Usage of ultrasonography to diagnose CTS has been the subject of investigations for many years. Superb microvascular imaging (SMI) is a newly developed ultrasonographic technique to visualise vascularity. More recently, there have been some studies on the diagnosis of CTS with SMI. However, a review of the literature reveals that there there has been no study on the diagnosis of CTS in PsA. This is the subject of the present report, where we evaluate the diagnostic value of SMI in CTS in patients with PsA.Materials and methods 30 PsA patients (56 wrists) and 26 healthy volunteers (52 wrists) were examined in the study. Demographic and clinical features were recorded carefully. All participants underwent a standard electrodiagnostic study (EDS) and ultrasonographic examination within a maximum of one week. CTS was diagnosed using EDS. The vascularity of the median nerve was examined using a new ultrasonographic technique. SMI signals were graded from 0 to 3.Results There were no significant differences between groups, with respect to their age, gender, body mass index, smoking status, and hand dominance. Although CTS was diagnosed in 9 patients (14 wrists) in the PsA group, CTS was not diagnosed for any patient in the control group (p=0.002). The blood flow display ratio of SMI in the median nerve was markedly higher in CTS patients than with controls (median (25th, 75th percentile): 2(0.75, 2), 1(0, 2); p=0.014; respectively) or compared with CTS-free PsA patients (2(0.75, 2), 1(0, 2); p=0.030; respectively). There was no remarkable difference between PsA patients and healthy controls with respect to the median nerve’s blood flow display ratio (median (25th, 75th percentile): 1(0, 2), 1(0, 2); p=0.164; respectively).Conclusion To the best our knowledge, this is the first study assessing SMI in the diagnosis of CTS in PsA patients. We concluded that SMI has important diagnostic value in PsA patients for diagnosing CTS.
Keywords: Psoriatic arthritis; carpal tunnel syndrome; median nerve; ultrasonography; superb microvascular imaging